Efficacy of China’s low-carbon agricultural pilot policy: a company-farmer analysis from the middle and lower yangtze river basin, China - Jia, Lei; Meng, Yuan; Liang, Hanzhong (Frontiers in Environmental Science, 2025)
China’s central government introduced the low-carbon agricultural pilot (LCAP) policy to curb carbon emissions and foster sustainable growth. While most research has centered on macro-level impacts (provinces and cities), this study uniquely examines the LCAP policy’s influence on agricultural companies’ environmental expenditures and farmers’ net income. Given the LCAP’s weak-constraining nature, its effectiveness at the company and farmer level remains intriguing. We apply the Propensity Score Matching–Difference in Differences (PSM-DID) method, which excels in mitigating sample selection bias, focusing on the 2011–2020 LCAP phase involving 34 listed companies in China’s agriculture and food sectors. Further, we analyzed data from 410 rice farmers in Hubei, Zhejiang, and Shanghai, assessing the LCAP’s effects on their income. Results reveal that companies in LCAP cities decrease their environmental spending by 0.91 points (1% significance). On the farming front, non-participation leads to a potential 28-thousand-yuan income reduction. Organic fertilizers, compost, and recycling cultivation waste prove impactful, promoting income and ecological sustainability. However, the effectiveness of high-cost, long-payback energy-saving machinery subsidies appears limited under current implementation conditions. These findings suggest a potential misalignment between policy design and implementation outcomes, highlighting the challenges associated with non-mandatory environmental policies such as the LCAP in achieving their intended objectives.